A STUDY ON E-MARKETING AND ITS IMPACT ON THE CONSUMER BEHAVIOUR WITH SPECIAL REFERENCE TO TIRUNELVELI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
Today, the world has become progressively more digital concentrated and is developing at a meaningfully faster rate. It is general at this moment to have automatic access to digital devises and the internet because of the digital capabilities obtainable that completely transformed the mode in which society communicates and interacts. The way in which digital marketing has accelerated since the 1990 and 2000 it, had significantly transformed the manner, how the brands and businesses utilize technology and digital marketing to enlarge value to their marketing efforts. The essential to market a brand over the comprehensive range of technology devices available has turn into a challenge for brands but nevertheless allows for additional means to reach and influence customers and their commitment with a brand.E-marketing drives are fetching more widespread, as digital platforms are more and more being unified into marketing plans. Digital platforms permit brands to be well storytellers and make available the customers with a space to share their experiences of brands and products. This paper intends to understand the E-marketing and its impact on the consumer behaviour- a study with special reference toTirunelveli District. The study has been made by conducting a survey in Tirunelveli District. For that, the researcher collected90samples from the respondents and percentage, Garret ranking method and t- test used for this study.